Analysis of the Influence of Selecting Project Implementation Methods on Project Success: Case Study of Competency Certificate Reminder Feature Development at PT Eleska Iatki - Mulyati, Rika; Suakanto, Sinung; Raharjo, Adi; Agustien, Ferry; Priyadi, Djoko (Informatics Engineering Department of Halu Oleo University, 2024)
Project success relies on effective management and efficient implementation methods. These methods optimize potential, overcome risks, develop timely plans, maintain quality, and manage budgets. A correlation analysis was conducted on four attributes: clarity, accuracy, effectiveness, selection of methods, and standard methods. The results showed a high correlation between project implementation methods and project success, indicating a significant impact on project success. PT Eleska Iatki, a business process provider, requires digital projects for competency certificate validity period reminders, emphasizing the importance of appropriate implementation methods for project success and company goals. Keywords; Project Management, Implementation Methods, Correlation, Chi-Square, Data Analysis